1997
DOI: 10.1139/v97-043
|View full text |Cite
|
Sign up to set email alerts
|

Keto–enol tautomerism, NMR spectra, and H–D exchange of 4-hydroxycoumarins

Abstract: 4-Hydroxycoumarin 1, 4,5-dihydroxycoumarin 2, and 4,7-dihydroxycoumarin 3 undergo H–D exchange at the C(3) atom of the lactone ring. Although only the 4-hydroxy-2-chromenone tautomeric forms are seen in the 1H and 13C NMR spectra of compounds 1–3, the equilibrium between the 4-hydroxy-2-chromenone and 2,4-chromandione forms is suggested to be the key step in the H–D exchange reaction. 4,5-Dihydroxycoumarin shows the highest rate of the reaction, since H-bonding between 5-hydroxyl and 4-keto functional groups c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 0 publications
4
24
0
3
Order By: Relevance
“…21 In addition, the tautomeric equilibrium of lactones has been studied and evidence of the enol tautomer occurrence has been found by 1 H and 13 C NMR. 22 There are several reports in the literature in regard to structural elucidation of organic compounds by mass spectrometry but few publications are found for the investigation of ketoenol tautomerism. From the latter, the analysis of the mass spectra of some β-diketones and the corresponding comparison among differently substituted analogues, led to the conclusion that fragmentation is strongly influenced by the keto-enol content of these compounds.…”
Section: Equationmentioning
confidence: 99%
“…21 In addition, the tautomeric equilibrium of lactones has been studied and evidence of the enol tautomer occurrence has been found by 1 H and 13 C NMR. 22 There are several reports in the literature in regard to structural elucidation of organic compounds by mass spectrometry but few publications are found for the investigation of ketoenol tautomerism. From the latter, the analysis of the mass spectra of some β-diketones and the corresponding comparison among differently substituted analogues, led to the conclusion that fragmentation is strongly influenced by the keto-enol content of these compounds.…”
Section: Equationmentioning
confidence: 99%
“…It was reported that the hydrazone NH proton resonance appears approximately between 13.0 and 16.0 ppm, in o-and p-hydroxyazo dyes [25,26]. Also, the spectral data do not show any more high field signals around 12.4 ppm which is reported for the O-H of form (A),(B) or around 5.5 ppm for CH of tautomeric form C of the annulated similar compounds, respectively [27]. It is noteworthy in this connection that the rule recently formulated by Lee et al [28] evidence that "While the low energy barrier for rotation around the C-N single bonds in the azo tautomer would give rise to a single set of resonances as a population-averaged signal, the restricted rotation around the C=N double bonds in the hydrazone form would lead to two distinctive geometric isomers".…”
Section: Synthesis and Tautomeric Structurementioning
confidence: 79%
“…Additionally, these kind of compounds is also extensively studied in analytical chemistry (Beldean-Galea et al, 2008;Bieganowska, 1997;Blahova et al, 2006;Cacciola et al, 2007aCacciola et al, , 2007bCacciola et al, , 2007cJandera et al, 2008Jandera et al, , 2005Jin et al, 2007;Joseph et al, 2009;Li and McGuffin, 2007;Meaney and McGuffin, 2008;Novakova et al, 2010;Spacil et al, 2008;Subbiah et al, 2005;Sun et al, 2009;Zhang et al, 2010) and other products of technical importance such as plant growth regulating modulators Brooker et al, 4 The proton NMR spectrum of 4-hydroxycoumarin (Traven et al, 1997a) (Table 1) revealed only one signal is observed as a singlet at 5.61 ppm, typical chemical shift for hydrogens on non-aromatic double bonds and no other signal is observed with the exception of the four aromatic hydrogens (H-5, H-6, H-7, H-8). It shows two complex multiplets, of equal intensity, at 7.66 and 7.84 ppm due to the C-5 and C-6 protons, and two others at 7.36 and 7.39 ppm for the C-7 and C-8 protons, respectively.…”
Section: Introductionmentioning
confidence: 99%